Zoo [videorecording (DVD)] - McIvor, Colin (Film director); Parkinson, Art, 2001-; Jones, Toby, 1966-; Wilton, Penelope, 1946- (Samuel Goldwyn Films, 2018)
Based on a true story, twelve-year-old Tom and his misfit friends fight to save Buster the baby elephant during the air raids on Belfast in 1941.